"You can Talk in Espagñol!": An Ethnographic case Study of an African-American Emergent Bilingual and Biliterate Identity. Issue 7 (2nd October 2020) - Bauer, Eurydice; Cárdenas-Curiel, Lucía; Ponzio, Christina
Abstract: This ethnographic case study explores the dynamic and fluid development of one African-American student's bilingual/biliterate identity through her enrollment in a Spanish-English Dual Language Education program. We integrate the frameworks of identity in interaction and monoglossic and raciolinguistic language ideologies to understand how this student approaches her Spanish language and literacy development from kindergarten to grade 5. The study documents the fluid nature of the focal student, Tamara's, identity as she journeyed from a Spanish enthusiast in kindergarten who embraced her emerging bilingualism/biliteracy to a student who seemed to question her identity as Spanish literate person. Specifically, we examine her affective response to developing bilingualism and biliteracy. We identify three paradoxical influences, or double-binds, in how she was differently positioned across multiple interactions as a bilingual African-American student.